Unexpected microbial metabolic responses to elevated temperatures and nitrogen addition in subarctic soils under different land-use - Schroeder, Julia; Peplau, Tino; Gregorich, Edward; Tebbe, Christoph C.; Poeplau, Christopher (Zenodo, 2022)
This study investigated how subarctic soils under different land use will respond to warming and increasing N availability to allow for better predictions of C cycling under global change. The short-term temperature sensitivity as well as N-input effects on microbial CUE, respiration, growth and turnover were assessed in a one-day incubation experiment according to the 18O-CUE approach. The warming and N response of SOM decomposition were assessed in a 50-days incubation experiment via measurement of cumulative respiration. Both experiments were conducted with the following three treatments: incubation at 10 °C, incubation at 20 °C, and incubation at 20 °C plus N-fertiliser addition at an amendment rate of 100 kg N ha-1. The response to warming or N addition were expressed as response ratios RRT = 20°C/10°C and RRN = 20°C+N/20°C for warming and N response, respectively. The R code was developed under R v3.6.3 and adapted to work under version R v.4.1.2. The repository includes the following files: general_soil_parameters_per_sample.csv - general soil data for each field sample (n=27) general_soil_parameters_per_plot.csv - general soil data assessed on pooled replicated field samples (n=9) respiration_over_50d_incubation.csv - respiration rate and cumulative respiration for each time-point and laboratory sample over the 50-days incubation sample_data.csv - data measured for each laboratory sample (n=81) Warming_and_nitrogen_response_of_CUE_in_subarctic_soils.Rproj - Rproject (load project to work on provided scripts and data) load_data_script.R - loads required data absolute_values_script.R - summary of absolute ranges of parameters per land-use type and site absolute_linear_mixed_effects_model_script.R - run statistical analysis correlograms_absolute_soil_params_script.R - correlation analysis to identify what drives absolute values plot_correlations_absolute_soil_params_script.R - plot drivers of CUE and cumulative respiration RRT_RRN_calculation_script.R - calculates response ratios plot_RRT_RRN_script.R - ...